Building paths to success: a multilevel analysis of the effects of an emotional intelligence development program on the academic achievement of future teachers - Poveda-Brotons, Rosa; Izquierdo, Andrea; Perez-Soto, Natalia; Pozo-Rico, Teresa; Castejón, Juan-Luis; Gilar-Corbi, Raquel (Frontiers in Psychology, 2024)
The situation generated by the recent pandemic has had several effects on education, one of them being the necessary but hasty efforts of teachers and students to adapt to the demands of a virtual classroom environment. Thus, it is essential to promote the development of digital competencies in future teachers, enabling them to create effective learning situations in the digital medium. Moreover, the European university curriculum includes a set of specific competencies (specific to each degree) and a series of generic competencies, many of which are related to emotional intelligence. Our work emerges from these specific premises and the more general need to develop emotional skills and learning abilities in virtual environments for future educators. The sample comprised 240 students in higher education, pursuing a bachelor's degree in education at the University of Alicante, Spain (68.3% were female and average age of the participants was 19.43 years (SD = 4.127). Using a quasi-experimental design with pretests, posttests, and a control group, we present the effects of an online program aimed at improving the emotional skills and academic performanceachievement of future teachers in higher education. In this study, a 30-hour emotional intelligence training program was implemented. Since the student sample was grouped into different classes, we analyzed, using a generalized linear mixedeffects model, whether students who took the program showed a significant improvement in their academic performanceachievement at the end of their studies, compared to those who did not take it. The results show a significant improvement in the academic performanceachievement at the end of the bachelor's degree studies of the students in the experimental group. These results open up a field of possibilities for the implementation of this type of training using virtual environments, enabling interventions to enhance the emotional development of the teaching staff (and, subsequently, in their students), develop their teaching careers adequately, and employ the ideal strategies to address educational programs. Looking ahead, the integration of emotional development programs that incorporate emerging technology into university curricula could enhance the preparation of educators profoundly and create adaptable learning environments for contemporary students.